THE RISKS OF THE FORMATION OF THE SOCIAL STATE IN THE RUSSIAN FEDERATION AND THE PROBLEM OF SOCIALIZATION OF CERTAIN SECTORS OF SOCIETY - I. Loskutova; M. Sinyaev (Вестник университета, 2019)
The article considers problems of formation of the social state in Russia and general problems of socialization of different groups of the population. The nature of modern society poses a number of problems in the area of socialization, as the innovative nature of society makes meaningless the traditional model of socialization based on the reproduction of established patterns. Skills are needed to make unconventional, independent decisions in conditions of constant changes of the social environment and the accompanying technosphere and the ability to build social networks independently or incorporated into existing ones. However, the society has already started to develop imbalances between those groups that have mastered these new competencies, and those that have so far been unable to do so. Hence the concept of the social state, one of the major challenges which, according to the authors, is to promote the socialization of various social groups.